Política do esporte de alto rendimento no Brasil: Analise da estrategia de investimentos nas confederacoes olímpicas - Mazzei, L. C.; Cunha Bastos, F.; Silveira Böhme, M. T.; de Bosscher, V. (Revista Portuguesa de Ciências do Desporto, 2014)
Brazil has invested intensively in high performance sport to seek success and better results at major international sporting events. One of the strategies adopted by the Brazilian government is transfer funds to organizations such as the Olympic national Federations. Through documental analysis of reports about resources utilization in the Federations from 2002 to 2012, the aim of this study was to analyse the evolution of this Brazilian strategy and compare it with international models that have focus in international sporting success. The results showed that the investment have been mainly used in the organization and participation in international sports competitions. On the other hand, there are worrying gaps for the development of high performance sport in Brazil, affecting the performance in the long term. Organizations responsible for high performance sport in Brazil should be aware of this type of study, as well as using more properly the example of other countries that have success in international competitive sport